Frail older adults' perceptions of an in-hospital structured exercise intervention. Issue 4 (December 2017) - O'Hare, Louise; Savage, Eileen; McCullagh, Ruth; Bantry White, Eleanor; Fitzgerald, Eilis; Timmons, Suzanne
Abstract: Background: Exercise interventions need to be assessed qualitatively to establish how people participate in and perceive the intervention and how interventions should be delivered for maximal effect. Objectives: To explore how frail older inpatients perceived the effects of a pilot augmented prescribed exercise programme (APEP). Design: An interpretive phenomenological design using open-ended semi-structured interviews. Data were analysed using thematic content analysis. Setting: An acute teaching hospital. Participants: Thirteen of the frail older adults who participated in the APEP. Results: The participants' perceived relationship with the interventionist was highly influential, affecting participation rates, perceived value of the APEP, and outcome expectations. Pre-existing positive outcome expectations increased the likelihood of fully engaging in the programme and valuing the outcomes. Barriers to the intervention included negative or no outcome expectations and fatalism. Recent exercise history affected their views of the APEP. Perceived positive outcomes included increased intention to exercise postdischarge, improved self-efficacy and perceived improvements in physical status. Conclusion: Exercise interventions targeting frail older adults in the acute setting may benefit from taking a multifaceted approach to implementation. Education tailored to the participants, and setting restorative goals, may improve outcome expectations and future intention to exercise. The relationship between the participants and those implementing an intervention appears critical to their participation and whether they value the programme.